Perwalian Anak Perempuan Hasil Zina Dalam Pernikahan (Studi Perbandingan Antara Mazhab Hanafi dan Peraturan Perundangan di Indonesia) : Studi Perbandingan Antara Mazhab Hanafi dan Peraturan Perundangan di Indonesia - Maryam Hanifah; Ahyat Habibi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
ABSTRACTOne of the noble sunnahs of Allah Ta'ala in the creation of humans is marriage, because when Allah Ta'ala created humans, Allah did not make them like wild reptiles, even Allah Ta'ala glorified humans by setting conditions that would fulfill their happiness and pleasure, always maintain his nobility, and that will be realized by marriage according to the Shari'a which will bind between men and women with noble ties. This sunnah is a bond that legalizes a deeper relationship between men and women on the terms that Allah Ta'ala shari'a has stated. Marriage is something that is very important, as well as the elements in it, such as guardianship in marriage, because guardianship is an element that will safeguard women's rights, glorify them, and protect them from foreign men who do not have sharia ties. over the woman. Among the scholars and jurists, namely hanafi and regulations in Indonesia, they have different views on the regulation of the requirements for marriage guardians, and they are among the well-known in matters of fiqh. Therefore, the author looks at the explanation of who has the right to be the guardian of the daughter of adultery according to the Hanafi school of thought laws and regulations in Indonesia. Because both of them have different special provisions in the matter of daughters resulting from adultery, such as guardianship, lineage and so on. Based on the results of the research and analysis, according to Hanafi, the guardianship of the daughter resulting from adultery in her marriage is al 'ashobah (the heir whose share is not determined, but can receive all of the assets or the remaining assets, after the assets are divided among the heirs of dzawil furudh) from the mother because he was assigned to his mother not from his father. As for when there is no 'ashobah for children who are underage, then it can be replaced by a male relative who is in the same uterus, then the leader or judge. If the girl is an adult, then she can marry herself without being accompanied by a guardian. Meanwhile, according to regulations in Indonesia, the guardian for a daughter resulting from adultery is a judge in the area where she lives.Keywords: Marriage Guardian; Daughters Resulting From Adultery; Law; Hanafi School; Indonesian regulations.